Probabilistic and deterministic estimates of near-field tsunami hazards in northeast Oman - El-Hussain, I. (2019)
Tsunamis generated along the Makran subduction zone (MSZ) threaten the Sur coast of Oman, according to deterministic and probabilistic analyses presented here. A validated shallow water numerical code simulates the source-to-coast propagation and quantifies the coastal hazard in terms of maximum water level, flow depth, and inundation distance. The worst-case source assumed for the eastern MSZ is a thrust earthquake of Mw 8.8. This deterministic scenario produces simulated wave heights reaching 2.5 m on the Sur coast leading to limited coastal inundation extent. Because Oman adjoins the western MSZ, the probabilistic analysis includes the effect of this segment also. The probabilistic analysis shows onshore inundations exceeding 0.4 km northwest of Sur where flow depths are likely to exceed 1 m in 500 years. Probability analysis shows lesser inundation areas with probability of exceeding 1 m flow depth up to 80% in 500-year exposure time. Teletsunamis are excluded from these analyses because far-field waves of the 2004 Indian Ocean tsunami did not impact the Sur coast. Also excluded for simplicity are tsunamis generated by submarine slides within or near MSZ rupture areas. The results of this research provide essential information for coastal planning, engineering and management in terms of tsunami hazard and an essential step toward tsunami risk reductions in the northwest Indian Ocean.